Fun Number Recognition Cards as a Learning Media to Count for 4-5 Years Old Children - Fitriani, Ulfa; Tabroni, Imam; Guilin, Xie; Jiao, Deng (Journal of Computer Science Advancements, 2023)
Mathematics education is a very important education. Early childhood is a golden age, namely the age of 0-6 years in Indonesia and abroad, namely at the age of 0-8 years. According to Jean Piaget, this has been the main reference for the kindergarten curriculum and even education in general. The first step is to design a fun number learning media with the latest literature. The design is tested by experts and validated according to the needs of students. The result of the author's initial observation in the field is that Amira kindergarten students aged 4-5 years do not globally understand the lack of development in the cognitive aspect of knowing numbers and symbolic thinking for effective results. %. Based on the discussion above, it can be concluded that playing while learning using cards recognizes cool numbers in improving six aspects of development in children aged 4-5 years at Amira Plered Purwakarta Kindergarten.